Elevated Endothelin-1 in Intradialytic Hypertension - Rubin Surachno Gondodiputro; Andika Wiratama; Stefanie Yuliana Usman; Erma Arnika Dewi; Evan Susandi; Afiatin Afiatin; Ria Bandiara (International Journal of Integrated Health Sciences, 2019)
Objective: To determine the relative change in endothelin-1 (ET-1) during hemodialysis procedure in Stage Five Dialysis-Dependent Chronic Kidney Disease (CKD-5D)patients with and without intradialytic hypertension (IDH).Methods: This was a cross-sectional, observational study involving 40 CKD-5D patients who received two hemodialysis per week for at least three months at the dialysis unit of Dr. Hasan Sadikin Hospital General Bandung, Indonesia during September 2016. Subjects were divided two groups: with IDH (n=20) and without IDH (n=20). Plasma ET-1 level was examined before and after hemodialysis.Results: There was a significant elevation of ET-1 level (mean±SD pg/mL) between pre- and post-dialysis state in patients with IDH (3.33±1.28 vs. 3.84±1.75; relative changes: 15.32%, p=0.013). No change was observed in patients without IDH (3.99±2.30 vs. 4.38±1.81; relative changes: 9.77% p=0.083). The post-dialysis absolute ET-1 level was significantly lower in CKD-5D patients with IDH (3.84±1.75 vs. 4.38±1.81; p=0.024).Conclusion: There was a significant elevation of ET-1 level in CKD-5D patients with IDH during hemodialysis procedure at the dialysis unit of Dr. Hasan Sadikin General Hospital Bandung.